MEMBANGUN KOMUNIKASI DIALOGIS DALAM DAKWAH ONLINE (STUDI KASUS WEBSITE CARIUSTADZ.ID) - Heny May Widiyawati; Baharudin Ardani; Canra Krisna Jaya (Program Studi Komunikasi Penyiaran Islam STID Mohammad Natsir, 2025)
This research analyzes the application of dialogic communication in digital da'wah through a case study of interactive features on the cariustadz.id website. The shift of da'wah to online spaces opens up opportunities for broad reach, but presents challenges in maintaining personal relationships and authentic dialogue. Using a qualitative case study approach, this research examines the Ask Ustadz, Personal Guidance, and Rating features. The results indicate two sides: the Personal Guidance feature supports dialogic and reflective relationships (in line with the I-Thou and Praxis concepts), while the assessment and donation system has the potential to create transactional relationships (I-It). In conclusion, digital technology needs to be designed so that it does not reduce da'wah to a functional service but rather maintains its dialogic and transformative value.